(untitled) (REMUNOM, 2025)
Urban dysfunctions are a reality in Brazilian cities, regardless of their hierarchy, and result in disruptions and accidents for their inhabitants. Efficient urban mobility has been a major challenge for small and medium-sized cities, given population growth, lack of planning, and absence of public transportation. To address this issue, it is necessary to seek structural alternatives that make cities more functional and sustainable. This study focuses on the municipality of Januária - MG, which has a large number of bicycles used for various trips, but lacks adequate cycling infrastructure. Therefore, the feasibility of introducing cycling infrastructure on Corredor Chicó de Imídio Street is proposed, through field immersion, qualitative and quantitative analysis of the segment, and the development of a proposal for a cycling infrastructure project for the area under study. The implementation of the proposed cycling infrastructure is essential for urban mobility to take place in an appropriate, safe, and efficient manner, meeting existing local demand and encouraging new trips.